Intensi Penggunaan Aplikasi Haji Pintar dalam Perspektif Theory of Planned Behaviour - Aprilia, Rachma; Arianty, Erny; Hadi, Miftahul (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the factors that influence users' interest in using the Haji Pintar application as described in the planned behavior theory. This research uses a quantitative approach. The target population consists of Haji Pintar application users, with sample data collected through an online questionnaire distributed using the incidental method, which is a type of non-probability sampling. We processed the collected data using descriptive and inferential statistical analysis, utilizing the SmartPLS software. The findings indicate that perceived usefulness has a positive and significant influence on the intention to use the Haji Pintar application. Overall, the use of the Haji Pintar application provides ease for users. The results of this study are expected to be used as considerations in the development and improvement of the Haji Pintar application.